Pelatihan Pembuatan Media Pembelajaran Bagi Guru SMP Negeri 1 Duampanua Kabupaten Pinrang - Chalid Imran Musa; W. Kristina Parinsi; Andi Tenri Pada Agustang; Dwi Anugerah Lestari Musa; Rusman Rasyid (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Partnership Program (CPP) aims to produce products that can be used as learning media that allow students to be active, creative and fun in their learning activities. In turn, it will increase the effectiveness and quality of the learning process. The form of activity in this community partnership program activity uses a training strategy involving 30 participants through lectures, discussions, demonstrations, practice, and observation methods. To assess the success of this program through indicators (1), participants' attendance rate during the extension process was up to 80%. (2) All extension activities are carried out in accordance with the plan following the proposal. (3) A statement of satisfaction from extension participants and the school. Implementing this CPP can increase teachers' knowledge and skills in creating and optimizing learning media in the teaching and learning process in the classroom. The participants' enthusiasm evidenced this in participating in these activities. Besides, CPP produces products in the form of 30 learning media that can be used in the classroom's teaching and learning process.